The Influence Of Leadership And Organizational Culture To Motivation And Employee Performance At University Of Nahdlatul Ulama Surabaya Indonesia - Soelistya, Djoko; Gamal, Ahmad (Archives of Business Research, 2018)
The role of human resources experienced very significant changes as a result of the existence of an increasingly complex environment changes. Globalization, development of information technology, democracy and freedom of the mass media is the driving part of the environment, so the complexity demanded of the organization or institution to always think of ways how to be able to adapt and even addressing environmental change so that capable and can continue to make operational organization. Then to address such environmental changes, organization or College must have the support of a qualified human resources and competent as well as adhere to the value of innovative, professional, open and flexible. Employee is deciding who becomes a resource for College success, because the achievements of an organization are not in spite of the achievements as well as the role of members who are involved in it. This research aims to demonstrate and analyze the influence of leadership and organizational culture to motivation and employee performance University of Nahdatul Ulama in Surabaya. The sample in the research this is the employee University of Nahdatul Ulama in Surabaya totaled 62 people. Method of data processing is using SEM (Equational Structure Modeling) with AMOS version 18. The result of discussions can be concluded that 1) Leadership significant effect on employee motivation University of Nahdatul Ulama Surabaya, 2) Organizational culture significant effect on employee motivation University of Nahdatul Ulama Surabaya, and 3) Motivation significant effect on the employee performance University of Nahdatul Ulama in Surabaya.